Sobukwe and the psychosocial - Hook, Derek (PINS-Psychology in Society, 2024)
The political writings of Robert Mangaliso Sobukwe, like those of Anton Muziwakhe Lembede and Steve Bantu Biko, are shot through with psychological notions (ideas of consciousness, mental emancipation, psychological enslavement, self-realization, the African personality, etc.). The use of such terms is not psychological in a strict disciplinary sense, yet it is nevertheless of crucial psychosocial relevance for a number of reasons. Firstly, such a borrowing of terms necessarily breaks down the partitioning of the psychical and the political. Secondly, by being extracted from the discourse of psychology and subjected to a psychosocial application, these terms are rendered politically operative and put to immediate socio-political use as part of the struggle against white supremacy. Thirdly, the psychological vernacular historically deployed by Sobukwe, Lembede and Biko, effectively called attention to aspects of the struggle not adequately foregrounded by political vocabularies of the time. It was in this way that the aligned discourses of African Nationalism and Black Consciousness as realized in the writings of Sobukwe, Lembede and Biko, sought to overcome an otherwise flawed mode of political resistance – the gradualist, petitioning stance of the African National Congress in the 1950s – with something altogether more radical.